Implementasi Kebijakan Kurikulum Merdeka pada Pengembangan Bakat dan Minat Siswa SD Negeri Kemakmuran 1 Songgom Brebes - Ikrimatul Aola; Nurfuadi (Jurnal Dirosah Islamiyah, 2024)
This research aims to describe the implementation of the independent curriculum policy in developing the talents and interests of students at SD Negeri Kemakmuran 1 Songgom Brebes. The author uses field research where researchers go directly into the field to obtain research data. The approach used is a descriptive qualitative approach to describe the implementation of the independent curriculum policy in developing the talents and interests of students at SD Negeri Kemakmuran 1. The data collection methods used in this research are interviews, observation and documentation. Next, the author analyzes the data using the Miles and Huberman model by reducing data, presenting the data and verifying the data. Then the data was tested for validity by data triangulation. The results of the research show that SD Negeri Kemakmuran 1 has implemented an independent curriculum to develop students' talents and interests, including: providing motivation to students, fostering enthusiasm for learning, paying attention to students, exploring family backgrounds, and establishing collaboration with student parents. SD Negeri Kemakmuran 1 also does several things to support children's talents and interests, including: drum band training, scout training and others. There are also several computer units and sports equipment.